2019
DOI: 10.4162/nrp.2019.13.2.95
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of Lycium barbarum on polarized human intestinal epithelial cells

Abstract: BACKGROUND/OBJECTIVES Inflammatory Bowel Disease (IBD) has rapidly escalated in Asia (including Korea) due to increasing westernized diet patterns subsequent to industrialization. Factors associated with endoplasmic reticulum (ER) stress are demonstrated to be one of the major causes of IBD. This study was conducted to investigate the effect of Lycium barbarum ( L. barbarum ) on ER stress. MATERIALS/METHODS Mouse emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Wawruszak et al demonstrated the anticancer effect of ethanol extract of goji berries (EEGB) on a human breast cancer cell line (T47D) [31]. Furthermore, the antiproliferative effect of goji berries was also reported in human colon cancer cell line Caco-2 [59,60], human hepatoma cell line QGY7703 [61], and human gastric cancer cell lines MGC-803 and SGC-7901 [62].…”
Section: Discussionmentioning
confidence: 99%
“…Wawruszak et al demonstrated the anticancer effect of ethanol extract of goji berries (EEGB) on a human breast cancer cell line (T47D) [31]. Furthermore, the antiproliferative effect of goji berries was also reported in human colon cancer cell line Caco-2 [59,60], human hepatoma cell line QGY7703 [61], and human gastric cancer cell lines MGC-803 and SGC-7901 [62].…”
Section: Discussionmentioning
confidence: 99%
“…Under ER stress, XBP1 mRNA can be processed to produce active transcription factors under the kinase and ribonuclease activity of IRE1α . Several studies found that the IRE1α–XBP1 pathway is involved in the inflammatory response. , IRE1α is the most conserved ER stress sensor, which regulates the generation of inflammatory factors via the activities of kinase and endoribonuclease in the C-terminal cytoplasmic moiety. As the downstream signal of IRE1α, XBP1 exerts a unique regulatory effect in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems that polysaccharides ( Lycium barbarum polysaccharides, LBPs), of which the fruit is particularly rich, are the primary bioactive components to determine the beneficial pharmacological effects of the berry [ 11 , 12 , 13 , 14 , 15 ]. Previous studies have shown that Goji berries have antioxidant, anti-aging [ 12 ], antitumoral [ 16 ], anti-inflammatory [ 17 , 18 ], immunomodulatory [ 19 ], gastrointestinal-protective [ 20 ], cardioprotective [ 13 ], retinoprotective [ 14 ], and neuroprotective properties [ 21 ] as well as beneficial effects on several aspects of the reproductive sphere [ 22 , 23 ]. Last but not least, an increasing number of studies are showing the influence of Goji berries on blood glucose level homeostasis, suggesting antidiabetic [ 15 , 24 , 25 , 26 , 27 ] and hypolipidemic effects [ 26 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%